Evaluation of Under-18 Marriage Permit Cases - Şahan, Uğur; Şenavcı, Murat; Erel, Özlem (The Bulletin of Legal Medicine, 2022)
Objective: Children marriage at early age appears to be a problem in many countries of the World nowadays. With this study, it is aimed to reveal the factors that are effective on the road to early marriage. Methods: In this research, it was examined on written reports to 151 cases who applied to Aydın Adnan Menderes University Hospital Forensic Medicine Department between January 01, 2007 and December 31, 2019 in Aydın. Results: It was determined that most of the cases (86,8%; n:131) were primary school graduates and 90,7% (n:137) did not continue formal education. 62,9% (n:78) of the cases were detected to apply for marriage after sexual intercourse or sexual abuse. The rate of those who became pregnant during their application and whose mothers gave birth at the age of 18 and under was 20% (n:20). There was a significant difference between pregnant women and their mothers first birth ages. Conclusion: Child marriage continues to be an important public health problem in our country and many other countries in the world. Obviously, multi-faceted strategies are needed to target different aspects of the problem, including legal, political, social, economic, health and education. Child marriage should be seen as a multidimensional, sequential abuse that affects both children giving births and children born from these marriages. This is an important form of the intergenerational abuse.